ANALYSIS OF ZAKAT COLLECTION AT BAZNAS OF NORTH SUMATRA PROVINCE BASED ON THE PRINCIPLES OF VOLUNTARISM AND PUBLIC WELFARE - Zein, Hanafi; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the effectiveness of zakat collection by the National Zakat Agency (BAZNAS) of North Sumatra Province, which is carried out based on voluntary principles from the perspective of maqashid sharia. This study uses a qualitative approach with a normative-empirical research type based on secondary data. Data were collected through a documentary study of official BAZNAS reports, local government publications, and scientific articles from nationally accredited journals. Data analysis was conducted descriptively and qualitatively with a thematic and normative approach, then examined within the framework of sharia objectives (maqashid sharia). The results show that although BAZNAS has implemented various strategies such as service digitization, zakat campaigns, and the involvement of religious leaders, the effectiveness of zakat collection is still low compared to the existing potential. The main factors affecting effectiveness include low public zakat literacy, weak trust in zakat institutions, limited institutional capacity, and minimal regulatory support at the regional level. In the perspective of maqashid sharia, the voluntary principle will have beneficial value if managed through a strong, professional system and impact on the empowerment of mustahik. Therefore, it is necessary to strengthen regional regulations, increase public literacy, and create institutional synergy so that zakat can become an effective and sustainable instrument of distributive justice.